Inventory of the library of Hermilio de Olóriz - Panizo Santos, Ignacio; San Martín Casi, Roberto (Huarte de San Juan. Geografía e Historia, 2016)
The authors publish the inventory of the private library of the Navarre historian Hermilio de Olóriz (1854-1919).